Gambaran Pengetahuan Dan Sikap Ibu Hamil Tentang Senam Hamil Di BPM Mona Durryah Siregar di Kota Padangsidimpuan - LUBIS, ARISA HARFA SAID; Nur Aliyah Rangkuti; Ayannur Nasution; Leli Khairani; Anwar Syahadat; Mona Durryah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2026)
ABSTRACT Pregnancy exercise is an exercise that is done to prepare and train muscles so that they can be used to function optimally during labor. Where the benefits include reducing complaints during pregnancy, cramps and back pain, improving sleep, making the body fresher and more relaxed and maintaining the flexibility of the abdominal wall and pelvic floor muscles during labor. The purpose of this study was to determine the description of the knowledge and attitudes of pregnant women about pregnancy exercise at the BPM Mona Durryah Siregar di Kota Padangsidimpuan. The type of research is quantitative with a descriptive design with a cross-sectional approach. The population in this study were all pregnant women in the third trimester at the BPM Mona Durryah Siregar di Kota Padangsidimpuan, as many as 43 people in May 2025. The sample in this study was all pregnant women in the third trimester at the BPM Mona Durryah Siregar di Kota Padangsidimpuan, as many as 43 people using the total sampling method. The analysis used was univariate with the results showing that the knowledge of pregnant women about pregnancy exercises was lacking knowledge as many as 22 people (51.2%), and the attitude of pregnant women about pregnancy exercises was negative as many as 28 people (65.1%). It is recommended that pregnant women increase their knowledge about pregnancy exercises so that their attitudes are more positive towards the benefits of pregnancy exercises. Keywords: Knowledge, Attitude, Pregnancy Exercise